2015
DOI: 10.1002/ppap.201500183
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Bi‐Maxwellian Distributions in a H2 Plasma Produced by a Narrow Gap VHF Discharge

Abstract: A capacitively coupled VHF H 2 plasma (60 MHz) was produced by a narrow gap discharge at high pressures, and spatial distributions of the plasma parameters were examined with the Langmuir probe. A bi-Maxwellian electron distribution was observed near the discharge electrode while a Maxwellian one near the center of the inter-electrode gap. The simulation using the PIC code showed that electrons had the Druyvesteyn-like distribution near the discharge electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…17, the Langmuir probe current-voltage (I-V ) curve indicated the existence of negative ions. In our recent studies, bi-Maxwellian electron distributions were observed near the discharge electrode, 29,30) where the temperature of low-energy electrons was around 1 eV. As is well known, many negative ions are generated in H 2 plasmas with T e ∼ 1 eV.…”
Section: That Hmentioning
confidence: 85%
See 1 more Smart Citation
“…17, the Langmuir probe current-voltage (I-V ) curve indicated the existence of negative ions. In our recent studies, bi-Maxwellian electron distributions were observed near the discharge electrode, 29,30) where the temperature of low-energy electrons was around 1 eV. As is well known, many negative ions are generated in H 2 plasmas with T e ∼ 1 eV.…”
Section: That Hmentioning
confidence: 85%
“…In our previous studies, the experimental results suggested the existence of negative ions in the 60 MHz VHF H 2 plasma. 17,18,28,29) Here, we calculated the axial profile of the H − density for different discharge gaps, where dissociative-attachment reactions of vibrational states were included. Figure 9 shows that the H − density has a maximum at the center and the maximum density is almost independent of the discharge gap distance and negligibly low.…”
Section: That Hmentioning
confidence: 99%